2016
DOI: 10.1111/nyas.12996
|View full text |Cite
|
Sign up to set email alerts
|

Acute stress and episodic memory retrieval: neurobiological mechanisms and behavioral consequences

Abstract: Episodic retrieval allows people to access memories from the past to guide current thoughts and decisions. In many real-world situations, retrieval occurs under conditions of acute stress, either elicited by the retrieval task or driven by other, unrelated concerns. Memory under such conditions may be hindered, as acute stress initiates a cascade of neuromodulatory changes that can impair episodic retrieval. Here, we review emerging evidence showing that dissociable stress systems interact over time, influenci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

13
166
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 180 publications
(193 citation statements)
references
References 218 publications
(615 reference statements)
13
166
3
Order By: Relevance
“…Although cortisol administration appears to bias cognitive processing in this way, we found that stress impaired cognitive inhibition. Second, our results provide only partial support for the perspective that stress impairs executive control and shifts cognition to a state of reactive or habitual action to facilitate adaptation to current circumstances (Gagnon and Wagner, 2016; Vogel et al, 2016). Although stress impaired almost all executive functions, stress enhanced response inhibition, which is inconsistent with the idea that stress impairs all executive control.…”
Section: Discussioncontrasting
confidence: 70%
See 3 more Smart Citations
“…Although cortisol administration appears to bias cognitive processing in this way, we found that stress impaired cognitive inhibition. Second, our results provide only partial support for the perspective that stress impairs executive control and shifts cognition to a state of reactive or habitual action to facilitate adaptation to current circumstances (Gagnon and Wagner, 2016; Vogel et al, 2016). Although stress impaired almost all executive functions, stress enhanced response inhibition, which is inconsistent with the idea that stress impairs all executive control.…”
Section: Discussioncontrasting
confidence: 70%
“…By impairing executive control of cognition (i.e., working memory, cognitive inhibition, and cognitive flexibility), stress contributes to a reactive cognitive state that is fine-tuned to rapidly consider highly salient (i.e., stressor-related) information (Gagnon and Wagner, 2016; Vogel et al, 2016). Our perspective is thus in agreement with models that suggests stress impairs executive control in order to force attention toward highly salient information (Vogel et al, 2016), but our perspective differs from these models by arguing that it is not all top-down control that is impaired by stress—only executive control of cognition is impaired, leaving executive control of motor actions intact.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This phenomenon has been replicated repeatedly (e.g., Buchanan et al, 2006; Smeets, 2011) even though, of course, non-significant effects and even the reversed pattern were reported (e.g., Wolf et al, 2002; Hupbach and Fieman, 2012). These non-replications may reflect a more moderate stress response and/or particularities of the learning material used in the studies (for reviews see Cadle and Zoladz, 2015; Gagnon and Wagner, 2016; Wolf, 2017). Studies in rodents revealed that this effect is caused by an interaction of a noradrenergic signal induced by the first response wave (the sympathetic nervous system) and a glucocorticoid signal induced by the second response wave (the hypothalamus-pituitary-adrenal (HPA) axis) (Roozendaal et al, 2006).…”
mentioning
confidence: 99%